Resurrecting Family Histories and Biographies for Members of the Society of Friends in Ireland : John Boles, a Case Study - Coutts, Peter J.F. (Brill Research Perspectives in Humanities and Social Sciences, 2024)
Irish Quaker biographers have focused on ministers, the influential and wealthy; many biographies are also unstructured and selective, leaving gaps in the narrative. The current work uses the life and family of John Boles (1661-1731), a Quaker stalwart for 50 years, as a case study for the biographer, introducing the major sources and showing how they can be deployed to 'resurrect' the contributions of the anonymous Quaker majority. As the biography is developed, information is explored and analyzed to construct reliable genealogical charts; information is culled from Friends' records to document the contributions and failures of family members in the context of their Quaker meetings; land records are consulted to measure and assess their gradual accumulation of wealth and the historical context is discussed as a backdrop to their evolving socio-economic status - all topics essential for comprehensive Quaker biographies and family histories.